(untitled) (Bangladesh Veterinarian, 2011)
An alternative to superovulation is in-vitro production (IVP) of embryos where the efficient collection and grading of oocytes is important. Ovaries from an abattoir were collected and categorized as type I with no corpus luteum (CL), and type II with CL. The length, width and weight of type I and type II ovary were 1.4 ± 0.03 and 1.5 ± 0.08 cm; 0.8 ± 0.04 and 1.0 ± 0.07 cm; 0.6 ± 0.07 and 0.7 ± 0.04 gm, respectively, each significantly (P<0.05) higher in type II ovaries. A total of 80 and 78 follicles were observed and 60 and 61 follicles aspirated from left and right ovaries, respectively, from each of 25 ovaries. Out of 133 follicles 100 were aspirated from 40 type-I ovaries, and 21 aspirated from 10 type-II ovaries. The differences in the number of normal, abnormal and total cumulus-oocytecomplex (COCs) per ovary between left and right ovaries were not significant (P>0.05). The number of normal (1.9 ± 0.11) and total (2.5 ± 0.14) COCs per ovary were significantly (P<0.05) higher in ovaries without than in those with CL (1.2 ± 0.36 and 2.0 ± 0.30, respectively). But the number (0.80 ± 0.13) of abnormal COCs per ovary was significantly (P<0.05) higher in ovaries with CL than in those without (0.7 ± 0.09). Significantly (P<0.05) higher percentage of COCs expansion was grade A (6.9 ± 2.05) than grade B (53.1 ± 1.27) COCs. It is suggested that type I (without CL) ovaries and follicles of 2-6 mm diameter are suitable to collect good quality COCs for in-vitro maturation (IVM) of oocytes and the culture condition for IVM of sheep COCs are reported. DOI: http://dx.doi.org/10.3329/bvet.v28i1.8811 Bangl. vet. 2011. Vol. 28, No. 1, 31-38